2020
DOI: 10.1021/acsaem.0c00026
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cr-Substituted CeO2Nanoparticles Synthesized Using a Non-equilibrium Supercritical Hydrothermal Process: High Oxygen Storage Capacity Materials Designed for a Low-Temperature Bitumen Upgrading Process

Abstract: As described herein, the synthesis of highly Crsubstituted CeO 2 nanoparticles (Cr-CeO 2 ) for low-temperature bitumen upgrading is demonstrated using a supercritical hydrothermal method including a subcritical region. A continuous flow reactor that can provide a non-equilibrium process was used to improve Cr substitution in the CeO 2 lattice. Consequently, a Cr-substitution concentration of 22.7 mol %, which was unobtainable using the equilibrium process (5.1 mol %), was achieved. As the Cr-substitution conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
1
17
1
Order By: Relevance
“…The NC sizes was determined by performing a Rietveld analysis of the XRD pattern and was calculated to be 7.8 nm in average for Crsubstituted CeO 2 NCs, a value that is slightly larger than the pristine CeO 2 NCs (average size, 6.6 nm). A prolonged reaction time in the supercritical water was acquired control the morphology and particle size of Cr-substituted CeO 2 , which is usually smaller than the pristine CeO 2 under the same synthetic condition [38]. The difference in particle size is probably attributed to the difference in surface energy similar to the previous study [53].…”
Section: 4theoretical Calculation Of the Effect Of The Cr Dopant On The E Vo Of Ceo 2 Ncssupporting
confidence: 64%
See 1 more Smart Citation
“…The NC sizes was determined by performing a Rietveld analysis of the XRD pattern and was calculated to be 7.8 nm in average for Crsubstituted CeO 2 NCs, a value that is slightly larger than the pristine CeO 2 NCs (average size, 6.6 nm). A prolonged reaction time in the supercritical water was acquired control the morphology and particle size of Cr-substituted CeO 2 , which is usually smaller than the pristine CeO 2 under the same synthetic condition [38]. The difference in particle size is probably attributed to the difference in surface energy similar to the previous study [53].…”
Section: 4theoretical Calculation Of the Effect Of The Cr Dopant On The E Vo Of Ceo 2 Ncssupporting
confidence: 64%
“…In this regard, Singh et al reported a promising system of Cr-doped CeO 2 nanoparticles, which contained a surprisingly high Cr dopant amount of 33% exhibiting flexible-valence states of hexavalent and tetravalent, resulting in a higher OSC performance and enhanced catalytic reactivity of oxygen evolution and hydrogen generation [36,37]. Recently, highly Cr-substituted CeO 2 NCs was also fabricated using a non-equilibrium supercritical hydrothermal process [38]. Furthermore, Cr-doped CeO 2 nanostructures with a small amount (less than 10%) and a low valence state of Cr 3+ , other than Cr 6+ with high toxicity, are also investigated and exhibit high reactivity in diverse processes, such as soot combustion, photocatalytic CO 2 reduction, and electrocatalytic N 2 fixation to NH 3 [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…SEM observations revealed that monodispersed Ca 3 Cr 2 Si 3 O 12 agglomerates with a popcorn quasi-spherical shape were the dominant morphology under the alkaline hydrothermal conditions. These agglomerates are constituted of tiny anhedral crystals, which self-assembled to produce the 3D hierarchical “popcorn” architecture [ 20 , 21 ]. The anhedral particle size varies from 12 to 34 nm, as suggested by the crystallite sizes calculated from SEM micrographs ( Figure 5 a,b) and the results given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Doped cerium dioxide (CeO 2 ) is one of the popular materials used for many application purposes as oxygen-ion conductor in solid oxide fuel cells, oxygen storage, three-way catalysts (TWC) for exhaust gas treatments from vehicles, as UV-blocking material for sun protection factor (SPF) in cosmetics, and as electrode material for different types of sensors. Cerium (Ce) atom reacts with oxygen and forms the two most stable structures that are CeO 2 (Ce 4+ ) and Ce 2 O 3 (Ce 3+ ), which exist in nature. For application purposes, the reduction of Ce 4+ to Ce 3+ and the creation of oxygen defects/vacancies in the host lattice play a vital role .…”
Section: Introductionmentioning
confidence: 99%